Breathless [videorecording (DVD)] - Davenport, Jack, 1973-; Dingwall, Shaun; Little, Natasha
Follows the lives of a group of doctors and nurses working in a London hospital, a world in which everything and everyone has their place. But underneath this veneer simmers a cauldron of lies and guilty secrets, driven by love, ambition and sex. Breathless opens in 1961, a time when Britain was on the brink of the '60s revolution, abortion is illegal and the contraceptive pill is only just available to married women.